Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.